Christ as performance: On Hans Urs von Balthasar's dramatic Christology from below - Havenga, Marnus (Stellenbosch Theological Journal, 2021)
This essay will explore Hans Urs von Balthasar's Christology as performance from below. It will begin by introducing Balthasar's theodramatic project as presented in his five-volume work Theo-drama. Here, it will be shown how Balthasar engages with and uses the conceptual resources of drama and the theatre to develop a theological dramatic theory with the performance of Christ at its very centre. This will be followed by an investigation into Balthasar's dramatic Christology and what he saw as the re-performance of the Christ-drama on the world stage. The essay will then conclude with a few brief remarks on the continued relevance of Balthasar's dramatic Christology, especially for those interested in doing “and performing“ theology from below.